RESPON PERTUMBUHAN DAN HASIL TANAMAN KAILAN PADA SUBSTRAT DAN KONSENTRASI AB MIX YANG BERBEDA - Astutik, Astutik; Anggarbeni, Susilo Ribut; Sutoyo, Sutoyo; A. F., Elisabeth (BUANA SAINS, 2023)
The research aims to determine the effect of the type of substrate and concentration of AB Mix on the results of kailan plants.  The research used a completely randomized design with eight treatment combinations, four replications, and three samples in each replication. The treatment combination are S1K1 (wood powder and AB Mix 4 ml/l); S2K1 (Sphagnum and AB Mix 4 ml/l); S3K1 (husk charcoal and AB Mix 4 ml/l); S4K1 (Cocopeat and AB Mix 4 ml/l); S1K2 (Wood powder and AB Mix 6 ml/l); S2K2 (Sphagnum and AB Mix 6ml/l); S3K2 (Charcoal husk and AB Mix 6 ml/l) and S4K2 (Cocopeat and AB Mix 6 ml/l). The results showed there is an interaction between the type of substrate and the concentration of AB Mix on the wet weight of the plant (your crop yield). The highest plant yields were obtained using husk charcoal substrate and AB Mix 6 ml/l. The husk charcoal substrate can produce the highest leaf area, but AB Mix 4 - 6 ml/l can not affect plant growth.